Low Uptake of Direct-acting Antiviral Therapy Among Hepatitis C Patients With Advanced Liver Disease and Access to Care, 2014-2017. Issue 1 (January 2021) - Spradling, Philip R.; Xing, Jian; Rupp, Loralee B.; Moorman, Anne C.; Gordon, Stuart C.; Lu, Mei; Teshale, Eyasu H.; Boscarino, Joseph A.; Schmidt, Mark A.; Daida, Yihe G.; Holmberg, Scott D.
Abstract : Goals: To determine the proportion and characteristics of adults with hepatitis C at health care organizations in 4 US states who initiated direct-acting antivirals (DAAs). Background: There are almost no data to assess the penetrance of treatment of the hepatitis C population in general US health care settings. Study: We conducted a prospective observational study using electronic clinical, pharmacy, and mortality data to determine the fraction of patients who initiated DAAs between January 2014 and December 2017, by start date and regimen. We used stepwise multivariate logistic regression analysis to identify sociodemographic and clinical characteristics associated with receipt of DAAs. Results: Of 8823 patients, 2887 (32.7%) received DAAs. Quarterly (Q) uptake ranged from 1.1% in Q3 2014 to a high of 5.6% in Q2 2015. Characteristics associated with receipt of DAAs included age 51 to 70 years, higher income, pre-2014 treatment failure, and higher noninvasive fibrosis score (FIB4); however, over one half of patients with FIB4 scores >3.25, consistent with severe liver disease, were not treated. A lower likelihood of initiation was associated with Medicaid coverage. Of 5936 patients who did not initiate treatment, 911 (15.3%) had died and 2774 (46.7%) had not had a clinical encounter in ≥12 months by the end of the study. Fewer than 1% of DAA prescriptions originated from nonspecialty providers. Conclusions: During 4 calendar years of follow-up, one third of patients initiated DAAs. Large fractions of untreated patients had advanced liver disease, died, or were lost to follow-up. Even among patients in integrated health care systems, receipt of DAAs was limited.